Exploiting Microscale Roughness on Hierarchical Superhydrophobic Copper Surfaces for Enhanced Dropwise Condensation. Issue 3 (7th January 2015) - Chen, Xuemei; Weibel, Justin A.; Garimella, Suresh V.
<x xml:space="preserve">Abstract</x> Hierarchical micro/nanostructured superhydrophobic surfaces are developed to control the nucleation, growth, and departure of condensate droplets on copper substrates. The microscale roughness elements on the hierarchical surface yield a 40% higher droplet growth rate and a 300% increase in cumulative droplet departure volume as compared to superhydrophobic surfaces with nanostructures alone. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>